A population‐wide perspective on the reach of substance use disorders: Parental exposure, diagnostic remission, and current disorders. Issue 1 (18th December 2021) - Na, Peter J.; Stefanovics, Elina A.; Rhee, Taeho Greg; Rosenheck, Robert A.
Abstract: Background and Objectives: Parental substance use disorder (SUD) increases the risk for childhood adversities. Lifetime and current SUDs are associated with functional impairment and psychiatric comorbidity. Research shows that these abate with diagnostic remission. However, a hierarchically ordered heuristic profile of adult subpopulations affected by SUDs has not been explored. Methods: We used data from the National Epidemiologic Survey on Alcohol and Related Conditions Wave III (NESARC‐III; N = 36, 309) to compare four subpopulations defined by the following hierarchy: (1) neither parental nor lifetime SUD (un‐affected group); (2) parental SUD but no personal SUD; (3) past but not current SUD (diagnostic remission); and (4) current SUD. We conducted bivariate comparisons and multivariable‐adjusted logistic regression to identify characteristics independently differentiating each group. Results: Almost half of the US adult population (108.9 million) were at risk from SUDs. Relative to the unaffected group (56.1%), the parental‐exposure‐only group (13.9%) experienced diverse parental and childhood adversities and increased risk for psychiatric disorders. Compared to the parental‐exposure‐only group those in the remitted group (14.1%) were more likely to report behavioral problems and lifetime psychiatric multimorbidities. Those with current SUD (15.9%) had a poorer mental health‐related quality of life. Discussion and Conclusions: This heuristic SUD hierarchy is associated with increasing adversities affecting almost half the US population, although only 15.9% meet the criteria for a current disorder. Scientific Significance: Our findings provide a rigorous population‐based estimate of the staggering public health impact of SUDs in the United States and suggest that almost half of the US population is either directly or indirectly affected by SUDs.